2005
DOI: 10.1161/01.res.0000194330.66545.f5
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Cardiac Progenitor Cells After Myocardial Infarction by Self-Proliferation and Selective Homing of Bone Marrow–Derived Stem Cells

Abstract: Tissue-specific progenitor cells contribute to local cellular regeneration and maintain organ function. Recently, we have determined that cardiac side-population (CSP) cells represent a distinct cardiac progenitor cell population, capable of in vitro differentiation into functional cardiomyocytes. The response of endogenous CSP to myocardial injury, however, and the cellular mechanisms that maintain this cardiac progenitor cell pool in vivo remain unknown. In this report we demonstrate that local progenitor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
166
2
9

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 9 publications
10
166
2
9
Order By: Relevance
“…My second point has to do with broadening the scope of this debate beyond just bone marrow, which I feel justified in doing since you invoked recent studies on reprogramming of somatic cells. My lab as well as many other well respected research groups have used selected c-kit+ cell populations derived from bone marrow as well as from other tissues that generate cells populations expressing various cardiogenic markers including those of cardiomyocytes following adoptive transfer to cardiomyopathically injured recipients [8][9][10][11][12]. While the process may be relatively inefficient at present, there is every reason to expect that the remarkable salutary effects mediated by adoptive transfer of stem cells in experimental animal models will readily be applied to translational therapy once underlying mechanisms are more fully understood.…”
Section: Murrymentioning
confidence: 99%
“…My second point has to do with broadening the scope of this debate beyond just bone marrow, which I feel justified in doing since you invoked recent studies on reprogramming of somatic cells. My lab as well as many other well respected research groups have used selected c-kit+ cell populations derived from bone marrow as well as from other tissues that generate cells populations expressing various cardiogenic markers including those of cardiomyocytes following adoptive transfer to cardiomyopathically injured recipients [8][9][10][11][12]. While the process may be relatively inefficient at present, there is every reason to expect that the remarkable salutary effects mediated by adoptive transfer of stem cells in experimental animal models will readily be applied to translational therapy once underlying mechanisms are more fully understood.…”
Section: Murrymentioning
confidence: 99%
“…26 CSP are able to transform to cardiomyocytes if interaction (not implying cell fusion) with adult cardiomyocytes is allowed. CSP can be derived from BMC 27 (see below). Cells expressing the homeobox gene islet-1 (isl-1) are also present in the adult heart, although in small number and restricted to the right side.…”
Section: Resident Stem Cellsmentioning
confidence: 99%
“…32 Regarding CSP, it has been shown that, after AMI, BMC home specific areas of myocardial injury and convert to CSP phenotype. 27 On the other hand, independent clonal studies have demonstrated that adult marrow stromal cells can originate the so-called cardiomyogenic cells (CMG), which differentiate to cardiomyocytes. 6,33 Among BMC, the stromal cells, often also called mesenchymal stem cells (MSC), seem more plastic than the other cell types regarding multilineage differentiation.…”
Section: Resident Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations